Christology, soteriology, and ethics in John and Hebrews: collected essays - Loader, William R.G. (Wissenschaftliche Untersuchungen zum Neuen Testament, 2022)
"This volume brings together essays on John and Hebrews by William R.G. Loader. Beside his monographs on John and Hebrews are numerous contributions to journals, conference volumes, and Festschriften, of which a representative selection is gathered here into a single volume. They discuss how these writings portray Jesus and his significance and deal with continuity and discontinuity with Israel's tradition, as well as address the ethical issues which these texts raise and also evoke."--